Sourcing & using Funds - a guide for the Caribbean entrepreneur - Eastmond, Everick M. (CCCRIS/CARICOM Project [Georgetown]GY, 1995)
Focuses on developing business plans, identifying sources of financing and technical assistance, and maximizing the use of funds.